Impacts of gender disparities in mental health and quality of life: A cross-sectional study of Brazilian physicians - Marcelo Gobbo Jr; Marina Silveira de Resende; Eduardo Cardoso Moura; Renata de Almeida Pedro; Isabelle Martins Santos (PLoS ONE, 2026)
Background Physicians are a professional group at high risk of impaired quality of life (QoL) and mental health due to heavy workloads, exposure to suffering, and structural inequalities. In Brazil, rapid feminisation of the medical workforce has not eliminated gender and regional disparities, and nationwide evidence on physicians’ QoL remains scarce. Methods This is a nationwide, cross-sectional, web-based survey of licensed physicians in Brazil between July and August 2024. Eligibility required active registration with a Regional Medical Council and prior use of a digital health platform. QoL was assessed using the WHOQOL-BREF, complemented by items on lifestyle, burnout, depression, and anxiety. Post-stratification weighting aligned the sample with the 2025 Brazilian Medical Census across sex and region. Weighted least squares regression models estimated unique contributions of sex, age, region, career stage, and mental disorders to QoL domains. Results A total of 2,005 physicians participated (56.1% women). Weighted WHOQOL-BREF scores post-stratification were 62.2 in the physical, 55.5 in the psychological, 56.5 in the social, and 63.6 in the environment domains, with a global score of QoL (defined as the mean of 0-100 four domains score) of 59.5. Women reported significantly higher prevalence of mental disorders (46.8% vs. 33.5% in men), particularly depression (25.3% vs. 17.7%) and anxiety (39.9% vs. 25.1%). QoL displayed a U-shaped trajectory across the life course, with lower scores in early and mid-career and recovery at older ages. Mental disorders were strongly associated with lower scores across all domains (–9 to –10 points in psychological and QoL, p < 0.001, large effect sizes). Multivariable models identified mental disorder as the dominant predictor of psychological and QoL perception outcomes, while sex explained variance in social relations, and region and age modestly contributed to physical and environment domains. Conclusions Brazilian physicians report lower QoL than both the general Brazilian population and international physician cohorts, with particular vulnerability in psychological well-being. Gender disparities persist, with women experiencing greater psychiatric morbidity despite higher social relations scores. Structural inequalities, workload, and dissatisfaction with the health system emerged as key stressors. Interventions should combine structural reforms, gender equity policies, and lifestyle-promoting strategies to support physician well-being.